Integrasi Basis Data Properti Menggunakan Metode Schema Matching Dengan Pendekatan Linguistic dan Constraint - Hariri, Muhammad; Triwijoyo, Bambang Krismono; Martono, Gallih Hendro (Universitas Bumigora, 2025)
Background: The rapid development of technology has driven progress across various sectors, including the property industry in Indonesia. However, property data integration on Lombok Island still faces challenges due to the diversity of attribute naming, which hinders efficient information retrieval.Objective: This study aims to integrate four property databases (Saduthama, Salva, SJP, and Garden View) using a schema matching method based on linguistic and constraint approaches.Methods: The linguistic approach is used to identify similarities between attributes, even when their names differ, using the Bigram technique, which proved effective in identifying attribute similarities with a threshold of 0.7. Meanwhile, the constraint approach evaluates the compatibility of attributes based on additional criteria such as data type, attribute length, null values, and uniqueness, ensuring that the integrated attributes work compatibly. The integration process includes preprocessing, generalization, and attribute matching.Result: The evaluation results show precision (P), recall (R), and F-measure of 90%, with an average accuracy of 84%.Conclusion: This result outperforms previous studies that achieved 100% precision, 60% recall, and 75% F-measure.